A do-it-yourself approach to achieving a flexible pressure sensor using daily use materials. Issue 39 (11th August 2021) - Duan, Zaihua; Jiang, Yadong; Huang, Qi; Yuan, Zhen; Zhao, Qiuni; Wang, Si; Zhang, Yajie; Tai, Huiling
Abstract : In order to solve the shortcomings of the complex manufacturing process and high cost of flexible pressure sensors, a low-cost and eco-friendly flexible pressure sensor is achieved using a simple do-it-yourself (DIY) approach. Abstract : Flexible pressure sensors with excellent pressure sensing performance have been developed rapidly in recent years, but they still suffer from the disadvantages of a complex manufacturing process and high cost. Here, a flexible paper-based (PB) capacitive pressure sensor is constructed by using daily use materials such as paper, polyester conductive tape and polyimide tape. Thanks to the simplicity of the fabrication method, the proposed PB pressure sensor can be even fabricated via a do-it-yourself approach. The rough surface microstructure of paper and polyester conductive tape endows the PB pressure sensor with good pressure sensing performance properties. Specifically, the optimized PB pressure sensor with two-sided microstructure interfaces exhibits a wide pressure detection range (0.1–80 kPa), an acceptable sensitivity of 0.23 kPa −1 (0.1–2 kPa), a low detection limit of about 3 Pa, fast response speed (∼41 ms at the finger tapping), and good durability (5000 cycles at 10 kPa). The pressure sensing mechanism of the PB pressure sensor is explained by analyzing the in situ cross-sectional optical photographs and video of the sensor at different pressures. Like many flexible pressure sensors based on complex technologies and high cost, the PB pressure sensor has also been successfully applied in many application scenarios ( e.g., finger bending, wrist pulse, nasal respiration, recording walking steps, early stage of Parkinson's disease, and proximity switch). Given the simple fabrication method, low cost and acceptable pressure sensing performance, we believe that the proposed PB pressure sensor is of extensive and practical application values in the field of wearable electronics and some underdeveloped areas, and is expected to help ordinary people become "home" engineers.